If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(7) + -1y = -8 Multiply -1 * 7 -7 + -1y = -8 Solving -7 + -1y = -8 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + -1y = -8 + 7 Combine like terms: -7 + 7 = 0 0 + -1y = -8 + 7 -1y = -8 + 7 Combine like terms: -8 + 7 = -1 -1y = -1 Divide each side by '-1'. y = 1 Simplifying y = 1
| .75x-.68x=.4 | | 0=3x^2-23x+30 | | -2÷-4/5 | | 10-6x=-4x+4 | | 2msquared+16=10m | | n/1.5=9 | | X^4+x^3-27x^2-3x-90=0 | | -4(3x-9)=8(-8-x) | | (-5x)+(-215)-(5x)+(21.5)= | | 3(3x-3)+2x=0 | | $200,000-1/10 | | 12-x=-38 | | 7x+4=4x+2 | | 9(-7)+8y=17 | | X+9y=-26 | | 2(x+4)=88 | | 3k+18=k+18 | | 168+8y=7x | | -34=v+5v-42 | | 18z+-14z-8=-30-6 | | 6x+4(2x+13)=136 | | -6(1-7n)=34+2n | | m/30=10/3 | | 1.5n=9 | | 2(7)+10y=-6 | | 3(h+7)=-18 | | (1/8)^2-2n=16 | | 2/s=7/9 | | 4cos^2(x)+2=5 | | 5x+2y=2x+4y | | 6(2x+8)-9x=0 | | 1.5(b+2)+3b=-1 |